Emerging and Re-emerging Infectious Diseases in ASEAN - Theerapuncharoen, Noppawan (Journal of Health Science of Thailand, 2017)
Revolutions in economic, social development and land use, speed and ease of travel and commerce, human demographics and behavior, and relocation of labor are major factors contributing to health problems in the ASEAN. The objective of this article were to compare and propose prevention and control measures of emerging and re-emerging infectious diseases in the ASEAN by reviewing previous literatures and online information using the terms “emerging infectious disease”, “re-emerging infectious disease”, and “ASEAN” as key words. The results revealed that the ASEAN had difficulties controlling and preventing emerging and re-emerging infectious diseases such as avian influenza, the 2009 H1N1 flu pandemic, ebola, SARS, MERS-CoV, dengue hemorrhagic fever, Zika, tuberculosis, malaria and AIDS, due to insufficient infectious epidemiology data, discrepancy in the efficacy of prevention and control of the diseases among ASEAN counties despite having the cooperative guidelines among ASEAN countries, lead national and international public health organizations. In this regard, the members of ASEAN countries should strengthen prevention and control by expanding collaboration with countries in other region, particularly those with well-developed disease control programmes.